2016
DOI: 10.3389/fneur.2016.00047
|View full text |Cite
|
Sign up to set email alerts
|

Antecedent Disease and Amyotrophic Lateral Sclerosis: What Is Protecting Whom?

Abstract: Multiple studies have shown that antecedent diseases are less prevalent in amyotrophic lateral sclerosis (ALS) patients than the general age-matched population, which suggests possible neuroprotection. Antecedent disease could be protective against ALS or, conversely, the asymptomatic early physiological underpinnings of ALS could be protective against other antecedent disease. Elucidating the impact of antecedent disease on ALS is critical for assessing diagnostic risk factors, prognostic outcomes, and interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(66 citation statements)
references
References 30 publications
4
58
2
1
Order By: Relevance
“…These conflicting results may be mainly due to methodological issues concerning the design and population of the study (single ALS centre cohort , case‐control study , population‐based register study , multiple ALS centre cohort in the present study), sample size (from 111 to 1439 patients with ALS and 2354 in our study) and study duration (covering a variable period up to 15 years ). Other methodological issues concern variables that have been taken into account: diverse diseases in some studies and only arterial hypertension and other cardiovascular diseases/risk factors in other studies. In contrast, our study considered almost all possible comorbidities and clinical diagnoses as indicated by referring neurologists, conferring more comprehensiveness to the assessment of comorbidities.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…These conflicting results may be mainly due to methodological issues concerning the design and population of the study (single ALS centre cohort , case‐control study , population‐based register study , multiple ALS centre cohort in the present study), sample size (from 111 to 1439 patients with ALS and 2354 in our study) and study duration (covering a variable period up to 15 years ). Other methodological issues concern variables that have been taken into account: diverse diseases in some studies and only arterial hypertension and other cardiovascular diseases/risk factors in other studies. In contrast, our study considered almost all possible comorbidities and clinical diagnoses as indicated by referring neurologists, conferring more comprehensiveness to the assessment of comorbidities.…”
Section: Discussionmentioning
confidence: 72%
“…To the best of our knowledge, only a few studies have considered the possible prognostic role of comorbidities related to the cardiovascular system. Hypertension was related to a late ALS onset in a cohort of 1439 patients, but none of the examined comorbidities significantly affected survival . Another study found that the presence of hypertension and coronary heart disease was associated with shorter survival at univariate analysis, findings that were not confirmed in multivariable analysis.…”
Section: Discussionmentioning
confidence: 96%
“…A low CKD prevalence is also consistent with ALS patients' significantly lower BMI. While there is no clear trend regarding the prevalence of comorbidities in our ALS study, the question of ‘what is protecting whom' [19] warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Given their high energy demand, motor neurons may be more sensitive than other cell types to energy deficits . An unfavourable vascular risk profile (eg, obesity and type 2 diabetes) has indeed been associated with a lower risk of ALS . Increased energy need may also simply constitute a compensatory mechanism secondary to neurodegeneration.…”
Section: A Summary Of Previous Studies On Blood Biomarkers Of Carbohymentioning
confidence: 99%